Evaluation of the spontaneous combustion tendency of corrosion products in oil tanks based on TOPSIS methodologies. (July 2021) - Liu, Hui; Hong, Rui; Lang, Zhihui; Yao, Jieyu; Ye, Dong; Shan, Jiangliang; Liu, Xin
Abstract: Spontaneous ignition of the corrosion products of an oil tank may lead to an explosion. To evaluate the spontaneous combustion tendency of corrosion products in oil tanks, the thermodynamic characteristic parameters of the corrosion products of oil tanks were obtained by thermogravimetry as evaluation indexes. Then, the objective weights of these indexes were calculated via the CRITIC method, and TOPSIS theory was used to comprehensively evaluate the spontaneous combustion tendency of corrosion product samples from oil tanks. The results show that the weight of the mass loss rate at the ignition point is the highest, and the apparent activation energy of the corrosion products is not the decisive factor affecting their spontaneous combustion tendency. As such, the spontaneous combustion tendency of the corrosion products of oil tanks cannot be based on only the apparent activation energy. The spontaneous combustion tendency of the corrosion products of a gasoline tank is lower than that of a diesel tank. The higher the heating rate is, the stronger the tendency of spontaneous combustion will be. Highlights: An evaluation method was proposed based on TOPSIS Methodologies. Evaluation indicators were determined by thermogravimetric analysis. The index with the highest weight is mass loss rate of ignition point. The E a of the corrosion products is not the decisive factor. The spontaneous combustion tendency of different corrosion products was presented.